Air quality changes after Hong Kong shipping emission policy: An accountability study. (July 2019) - Mason, Tonya G.; Chan, King Pan; Schooling, C. Mary; Sun, Shengzhi; Yang, Aimin; Yang, Yang; Barratt, Benjamin; Tian, Linwei
Abstract: Background: On July 1st, 2015, Hong Kong became the first city in Asia to implement a policy regulating sulfur dioxide (SO2 ) in shipping emissions. We conducted an accountability study assessing the improvement in ambient air quality and estimating the effect on health outcomes of the policy. Method: We used interrupted time series (ITS) with segmented regression to identify any change in ambient concentrations of SO2 in contrast to other ambient pollutants (particulate matter <10 μm in diameter (PM10 ), nitrogen dioxide (NO2 ) and ozone (O3 )) at 10 monitoring stations in Hong Kong from 2010 to 2017. We validated these findings using cumulative sum control (CUSUM) charts. We used a validated risk assessment model to estimate effects of changes in air quality on death for natural causes, cardiovascular and respiratory diseases. Results: Mean monthly concentrations of SO2 fell abruptly at the monitoring station closest to the main shipping port (Kwai Chung (KC)) by −10.0 μgm 3 p-value = 0.0004, but not elsewhere. No such changes were evident for the other pollutants (PM10, NO2, O3 ). CUSUM charts confirmed a change in July 2015. Estimated deaths avoided per year as a result of the policy were 379, 72, 30 for all natural causes, respiratory and cardiovascular diseases respectively. Conclusion: Implementation of the shipping emission policy in Hong Kong successfully reduced ambient SO2, with the potential to reduce mortality. However, to gain full benefits, restrictions on shipping emissions need to be implemented throughout the region. Graphical abstract: Image 1 Highlights: Shipping emission policy resulted in a reduction in SO2 at the main shipping port in Hong Kong by almost 50%. Other benefits included a reduction in PM10 by 20%. The policy reduced air pollution related deaths. Full benefits of the policy can only be accomplished if it is enforced regionally and not just in Hong Kong.